Experience of application of proproceptive modeling of walking in children of early age with motor disorders - A. G. Prityko; N. V. Chebanenko; V. P. Zykov; P. L. Sokolov; E. A. Bukreeva; T. A. Sednenkova; E. Yu. Sergeenko (Русский журнал детской неврологии)
Background. In the pathogenesis of cerebral palsy, the pathology of the proprioceptive modality plays an important role. Proprioceptive correction is an effective method for habilitation of children suffering from this disease. "Stimulation of the feet" is one of the methods of proprioceptive correction. In the process of treatment, pressure is applied to the receptor zones of the feet with pneumatic elements. The pressure is produced in walking mode and simulates the effect of the step on the foot. Objective: the rehabilitation treatment of children with the consequences of perinatal damage to the central nervous system and various forms of cerebral palsy.Materials and methods. The results of the rehabilitation treatment of 51 children with the consequences of perinatal damage to the central nervous system in 2 age groups: from 7 months to 1 year and from 1 year to 2 years are described. The average age of children was 1.8 ± 0.054 years, standard deviation 0.385. Among them, 27 (52.9 %) were boys, 24 (47.1 %) girls. The children had various motor dysfunctions. Children with a predominance of spasticity in the muscles of the lower extremities were 70.6 %, children with a predominance of reduced tone in the muscles of the lower extremities were 29.4 %. Rehabilitation treatment was carried out from the simulator of the base load "Сorvit". The course of basic stimulation was 10 procedures lasting from 10 to 15 minutes. The mode of stimulation was selected individually as in the classroom for physiotherapy. The duration and intensity of the pressure on the foot were selected.Results. As a result of treatment, positive dynamics of motor functions was noted. It was expressed in the normalization of muscle tone and with its decrease, and with an increase. The effect of tonic reflexes decreased. In the older group, normalization of the step structure was revealed. A reliable positive dynamics of speech and mental development was recorded. In children aged 7 months to a year with severe spastic paresis, it was statistically significant (p <0.05).Conclusions. Support stimulation is an effective and safe method of physical habilitation of children with the effects of perinatal brain lesions and cerebral palsy.